EDUCATION SOFTWARE DESIGN OF FACULTY ROOM FOR ENERGY EFFICIENCY - Reza Giga Isnanda (Jurnal Penelitian dan Pengembangan Komunikasi dan Informatika, 2015)
Nowadays, Global Warming has become a new issue whom impact can be very devastating and can threat the earth and human existence in the future. Since the impact can be very dangerous, many efforts have been done and many ideas have been proposed to prevent and reduce the effect of Global Warming. One of them is to introduce the importance of energy saving. This paper reports on the process of design and development of the prototype of an alternative solution which implement serious game to introduce to the user the importance of buying appliances which can consume energy efficiently Keywords: Educational software, serious games, energy efficient, Global Warming prevention